Some features of the formation of the theory of sports - Asatillayevich , A. B. (Proximus Journal of Sports Science and Physical Education, 2024)
At the present stage of development of the theory of sports, the solution of the problem of its application, proceeding from the need to improve the system of mass physical training of the population, is becoming increasingly important. At the same time, when starting to solve a particular applied problem in the field of sports, in our opinion, it is important to preserve the scientific methodology laid down by domestic scientists in the field of theory and methodology of physical culture.